Your heart belongs to me - Koontz, Dean R. (New York : Bantam Books, 2008)
For thirty-four-year-old Ryan Perry, life is good a year after the heart transplant that had saved him from certain death, until he begins to receive strange messages united by the theme, "Your heart belongs to me," and discovers that he is being stalked by a mysterious woman who bears a striking resemblance to the donor of his heart.
Keywords: Heart -- Transplantation -- Patients -- Fiction; Organ donors -- Fiction